From Stranded Praos ‘up to’ People Trailed by the Sea Stream: A Study about the Maritime Oral Tradition as a Source in the Writing about the Migration History in the Region of the Sawu Sea in the Lesser Sunda Islands - Didik Pradjoko (JMSNI (Journal of Maritime Studies and National Integration), 2017)
This research is about the migration history in the Sawu Sea Area, the Lesser Sunda Islands which made use of the oral tradition as its main source. For this purpose, this research can also be looked upon as a research in the maritime history which source is based on non-written sources. One can say that this topic has been much felt as not much important in the research on indigenous studies in particular in the areas outside Java so far. For this reason, this research is an effort to go beyond the conventional habit which is so far has been based on written sources (documents). In line with the applying of the oral tradition created a new genre the nonconventional historical genre which put the stress on the ‘mentalite’ of the people (society) which it studies. Although it is concerned with the local environment, this study also contributes to the national Indonesian history which it is hoped could strengthen the national integrity.